2008
DOI: 10.1111/j.1365-2222.2008.02982.x
|View full text |Cite
|
Sign up to set email alerts
|

Human innate immune responses to hexamethylene diisocyanate (HDI) and HDI–albumin conjugates

Abstract: Background-Isocyanates, a leading cause of occupational asthma, are known to induce adaptive immune responses; however, innate immune responses, which generally precede and regulate adaptive immunity, remain largely uncharacterized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 56 publications
3
46
0
Order By: Relevance
“…Other aspects of innate immunity in diisocyanate sensitization and asthma have been discussed previously. For example, it has been shown that HDI-albumin conjugates induce human chitinase-1, which may participate in a pattern-recognition receptor (PRR) reaction (Wisnewski et al, 2008). Additional indications include CD14 gene polymorphism associations to diisocyanate asthma (Bernstein et al, 2011), and the finding that MDI-GSH reaction products induce e.g.…”
Section: Discussionmentioning
confidence: 98%
“…Other aspects of innate immunity in diisocyanate sensitization and asthma have been discussed previously. For example, it has been shown that HDI-albumin conjugates induce human chitinase-1, which may participate in a pattern-recognition receptor (PRR) reaction (Wisnewski et al, 2008). Additional indications include CD14 gene polymorphism associations to diisocyanate asthma (Bernstein et al, 2011), and the finding that MDI-GSH reaction products induce e.g.…”
Section: Discussionmentioning
confidence: 98%
“…The data available suggest that the T cell subsets and the cytokine profile involved in LMW-induced OA may differ from those operating in atopic asthma. Although some of them induce IgE-mediated responses,34 most induce asthma by immunological mechanisms that are unrelated to IgE35 36 and in which non-adaptive immune responses may play a role 37. The possible role of non-immunological mechanisms such as epithelial injury, the remodelling of the airway wall, oxidative stress or neurogenic inflammation is currently being debated 38.…”
Section: Discussionmentioning
confidence: 99%
“…133 Taken together, these observations are consistent with the hypothesis that isocyanateinduced upregulation of immune pattern-recognition receptors by monocytes and release of damage-associated molecular patterns from injured epithelium may be a mechanism by which isocyanates stimulate the human innate immune responses and consequently influence the hypersensitivity reactions. 67 …”
Section: Ige-independent Immune Responsementioning
confidence: 97%
“…66 The responses of lysosomal genes were reported for in vitro experiments on human PBMCs and clinical studies of subjects before and after a specific inhalation challenge with HDI. 67 Significant changes in microarray gene expression were noted in lysosomal genes, especially peptidases and proton pumps involved in antigen processing. Another interesting finding was the exposure-dependent decrease in serum concentrations of chitinase 3-like-1 in subjects who lack the major (type 1) human chitinase (because of genetic polymorphism), but not in individuals possessing at least 1 functional chitinase-1 allele.…”
Section: Genetic Aspectsmentioning
confidence: 98%